Visual Rhetorical Studies Documentary It Might Get Loud - Tarmawan, Irwan; Priamanggala, Muhammad Fariz (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to prove that there is continuity between visual rhetoric theory and the three characters who convey messages to worthy khals through actions that have symbolic meaning. Film as an audio-visual language to feel joy, sadness, enthusiasm, and other emotions and feelings when the audience watches the film. Every film has a message to interpret and interpret something, even with the emergence of the documentary film genre which can factually inform a condition in the past. The film It Might Get Loud by Davis Gugenheim in 2008 with the documentary film genre rhetorically provides information about the development of music and musical genres from time to time. And in visual rhetoric theory there is a visual rhetorical perspective to understand the visual arguments of the three figures and in the end symbols can appear to produce meaning in the Documentary Film It Might Get Loud.